Economics of the tribes and their transformation - Singh, K. S. (ed.) (New Delhi, 1982)
The present volume seeks to present probably for the first time an all-India conspectus of the economies of the tribes through specific case studies from different parts of the country of various modes of production.
Keywords: Economics-Transformation; IAS as an editor